How Balinese Adolescents Perceived Romantic Relationship: How Balinese Adolescents Perceived Romantic Relationship - Dewi Arum Widhiyanti Metra Putri; Kwartarini Wahyu Yuniarti; Wenty Marina Minza; Bagus Riyono (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2020)
The romantic relationship is an interesting topic to study because it emerges as an important part of adolescent development that becomes increasingly important in subsequent years of individual development. One of the limitations of research in this field is the difficulty of providing unique and standards definitions of romantic relationships due to cultural differences in conceptions and the differences within individuals from the same cultural group. This study aims to explore the concept of a romantic relationship from the perceptions of Balinese adolescents and terms that represent it that can be used as a basis to comprehend the dynamics of romantic relationships in Balinese culture nowadays. Two phases of the study conducted through survey and FGD. Balinese adolescents were aged 15-17 years old (n= 277). Through thematic analysis procedures, some emergent themes were identified as romantic relationship conceptualization. This relationship was conceptualized as an exclusive relationship, consisting of affective, cognitive, and psychomotor dimensions, and was represented by many terms. This study concluded that the concept of romantic relationships for each individual from the same cultural group could be perceived differently, leading to varied forms of adolescents' behavior.